The Associate between Energy-Adjusted Dietary Inflammatory Index and Periodontal Disease: A Cross-Sectional Study - Hosseini, Hanie; Askari, Mohammad Javad; Rouhani, Hossein; Nikbakht, Mohammad Hossein; Shirban, Farinaz; Bagherniya, Mohammad; Askari, Gholamreza (International journal of preventive medicine, 2024)
Previous studies have shown that the dietary inflammatory index (DII) is associated with different health outcomes. However, few studies have investigated the relationship between DII and oral health. We aimed to assess the association between energy-adjusted dietary inflammatory index (E-DII) and periodontal disease. This cross-sectional study was conducted in 2019 on 213 Iranian participants. E-DII was calculated based on the data obtained by the food frequency questionnaire. The plaque control index was measured by the O'Leary method. Gingivitis was evaluated based on the signs of inflammation in the gums. The Decayed, Missing, and Filled Teeth (DMFT) are based on the number of decayed, filled, and missed teeth resulting from caries. the score of E-DII among subjects in the last tertile of the E-DII was ≥ -0.33/. Therefore, participants of the present study did not consume a high proinflammatory diet. No significant correlation between E-DII and dental plaque control index (r = 0.046, = 0.518), gingival index (r = 0.001, = 0.998), and DMFT (r = -0.021, = 0.762) was observed. In this study, inflammatory diet and plaque and gingival index were not associated; it should also be investigated in prospective studies.